Safety of BNT162b2 or CoronaVac COVID-19 vaccines in patients with heart failure: A self-controlled case series studyResearch in context - Xuxiao Ye; Caige Huang; Yue Wei; Silvia T.H. Li; Vincent K.C. Yan; Kai-Hang Yiu; Hung-Fat Tse; Tiantian Ma; Xiwen Qin; Celine S.L. Chui; Francisco T.T. Lai; Xue Li; et al. (Elsevier, 2023)
Summary: Background: COVID-19 vaccines are important for patients with heart failure (HF) to prevent severe outcomes but the safety concerns could lead to vaccine hesitancy. This study aimed to investigate the safety of two COVID-19 vaccines, BNT162b2 and CoronaVac, in patients with HF. Methods: We conducted a self-controlled case series analysis using the data from the Hong Kong Hospital Authority and the Department of Health. The primary outcome was hospitalization for HF and the secondary outcomes were major adverse cardiovascular events (MACE) and all hospitalization. We identified patients with a history of HF before February 23, 2021 and developed the outcome event between February 23, 2021 and March 31, 2022 in Hong Kong. Incidence rate ratios (IRR) were estimated using conditional Poisson regression to evaluate the risks following the first three doses of BNT162b2 or CoronaVac. Findings: We identified 32,490 patients with HF, of which 3035 were vaccinated and had a hospitalization for HF during the observation period (BNT162b2 = 755; CoronaVac = 2280). There were no increased risks during the 0-13 days (IRR 0.64 [95% confidence interval 0.33-1.26]; 0.94 [0.50-1.78]; 0.82 [0.17-3.98]) and 14-27 days (0.73 [0.35-1.52]; 0.95 [0.49-1.84]; 0.60 [0.06-5.76]) after the first, second and third doses of BNT162b2. No increased risks were observed for CoronaVac during the 0-13 days (IRR 0.60 [0.41-0.88]; 0.71 [0.45-1.12]; 1.64 [0.40-6.77]) and 14-27 days (0.91 [0.63-1.32]; 0.79 [0.46-1.35]; 1.71 [0.44-6.62]) after the first, second and third doses. We also found no increased risk of MACE or all hospitalization after vaccination. Interpretation: Our results showed no increased risk of hospitalization for HF, MACE or all hospitalization after receiving BNT162b2 or CoronaVac vaccines in patients with HF. Funding: The project was funded by a Research Grant from the Food and Health Bureau, The Government of the Hong Kong Special Administrative Region (Ref. No. COVID19F01). F.T.T.L. (Francisco T.T. Lai) and I.C.K.W. (Ian C.K. Wong)'s posts were partly funded by the D24H; hence this work was partly supported by AIR@InnoHK administered by Innovation and Technology Commission.